Acid‐Promoted Hydroformylative Synthesis of Alcohol with Carbon Dioxide by Heterobimetallic Ruthenium‐Cobalt Catalytic System. Issue 7 (12th March 2019) - Zhang, Xuehua; Tian, Xinxin; Shen, Chaoren; Xia, Chungu; He, Lin
Abstract: The acid‐aided heterobimetallic ruthenium‐cobalt catalytic system for the reductive hydroformylation with carbon dioxide was established. Various alkenes, including waste from biomass and petroleum industry, could be upgraded to valuable alcohols with this protocol. Acid‐promoted reverse water‐gas shift (RWGS), thereby accelerating the hydroformylative synthesis of alcohol. The theoretical computations revealed that acid promoted RWGS by facilitating the dehydroxylation of ruthenium hydroxy carbonyl intermediate. Abstract : Accelerated by acid : The acid‐aided heterobimetallic ruthenium‐cobalt catalytic system exhibited good performance in the hydroformylative synthesis of alcohols with carbon dioxide. The applicability of the valorization of industrial waste was highlighted. Experiments and theoretical computations demonstrated that addition of acetic acid could effectively accelerate the reductive hydroformylation by promoting reverse water‐gas shift.